Research advances of ferroptosis in renal diseases - Yu Peng; Wang Ting-ting; Liu Hong-bao (Linchuang shenzangbing zazhi)
Ferroptosis is characterized by intracellular iron overload and an accumulation of reactive oxygen species leading to lipid peroxidation.Although ferroptosis is more extensively discussed for acute kidney injury and renal cell carcinoma, its potential role in chronic kidney disease should not be ignored.Here the mechanisms of ferroptosis were summarized from the perspectives of iron, reactive oxygen species（particularly lipid peroxides）,amino acids metabolism, acute kidney injury, renal fibrosis, polycystic kidney disease, diabetic kidney disease and renal cell carcinoma.